Comparative Genomic Study of Vinyl Chloride Cluster and Description of Novel Species, Mycolicibacterium vinylchloridicum sp. nov. - Cortés-Albayay, Carlos; Sangal, Vartul; Klenk, Hans-Peter; Nouioui, Imen (Frontiers in Microbiology, 2021)
Advanced physicochemical and chemical absorption methods for chlorinated ethenes are feasible but incur high costs and leave traces of pollutants on the site. Biodegradation of such pollutants by anaerobic or aerobic bacteria is emerging as a potential alternative. Several mycobacteria including Mycobacterium aurum L1, Mycobacterium chubuense NBB4, Mycobacterium rhodesiae NBB3, Mycobacterium rhodesiae JS60, M. smegmatis JS623 have previously been described as assimilators of vinyl chloride (VC). In this study, we compared nucleotide sequence of VC cluster and performed a taxogenomic evaluation of these mycobacterial species. The results showed that the complete VC cluster was acquired by horizontal gene transfer and not intrinsic to the genus Mycobacteria senso lato. These results also show the presence of an additional xcbF1 gene that seems to be involved in Coenzyme M biosynthesis, which is ultimately used in the VC degradation pathway. Furthermore, we suggest for the first time that S/N-Oxide reductase encoding gene is involved in the dissociation of the ssuABC transporters from the organosulfur, which play a crucial role in the Coenzyme M biosynthesis, from. Based on genomic approach, M. aurum L1, M. chubuense NBB4, M. rhodesiae NBB3, M. rhodesiae JS60, M. smegmatis JS623 were misclassified and form a novel species within the genus Mycobacterium senso lato. Mycobacterium aurum L1 (DSM 6695 T = CECT 8761T) was the subject of polyphasic taxonomic studies. Phenotypic, chemotaxonomic and genomic data call for considering strain L1 as a type strain of novel species with the proposed name, Mycolicibacterium vinylchloridicum sp. nov.